Gene mutations and clonal architecture in myelodysplastic syndromes and changes upon progression to acute myeloid leukaemia and under treatment. (5th July 2018) - Stosch, Juliane M.; Heumüller, Anezka; Niemöller, Christoph; Bleul, Sabine; Rothenberg‐Thurley, Maja; Riba, Julian; Renz, Nathalie; Szarc vel Szic, Katarzyna; Pfeifer, Dietmar; Follo, Marie; Pahl, Heike L.; Zimmermann, Stefan; et al.
Summary: Knowledge of the molecular and clonal characteristics in the myelodysplastic syndromes (MDS) and during progression to acute myeloid leukaemia (AML) is essential to understand the disease dynamics and optimize treatment. Sequencing serial bone marrow samples of eight patients, we observed that MDS featured a median of 3 mutations. Mutations in genes involved in RNA‐splicing or epigenetic regulation were most frequent, and exclusively present in the major clone. Minor subclones were distinguishable in three patients. As the MDS progressed, a median of one mutation was gained, leading to clonal outgrowth. No AML developed genetically independent of a pre‐existing clone. The gained mutation mostly affected genes encoding signalling proteins. Additional acquisition of genomic aberrations frequently occurred. Upon treatment, emergence of new clones could be observed. As confirmed by single‐cell sequencing, multiple mutations in identical genes in different clones were present within individual patients. DNA‐methylation profiling in patients without identification of novel mutations in AML revealed methylation changes in individual genes. In conclusion, our data complement previous observations on the mutational and clonal characteristics in MDS and at progression. Moreover, DNA‐methylation changes may be associated with progression in single patients. Redundancy of mutated genes in different clones suggests fertile grounds promoting clonal selection or acquisition.